IMPLEMENTATION OF TEACHER DEVELOPMENT TO IMPROVE MATHEMATICS LEARNING ACHIEVEMENT USING C3T METHOD AND PEER TUTORING AT SDN PURWOMARTANI - Mursitowati, Nanik; Havifah, Banun; Khosiyono, Cahyo (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2024)
The impact of the perception that mathematics lessons are challenging and tedious is the low motivation of students to solve mathematics problems, which leads to low achievement of learning mastery. The activity focuses on implementing the C3T method and peer tutoring to improve the mastery of mathematics learning for 6th-grade students at SDN Purwomartani. The research method used is qualitative. The activity results show an improvement in the learning mastery of students from 9 students to 27 students, with 1 student receiving remedial action outside of class hours. There is a significant improvement in students’ learning success. It indicates that the C3T method and peer tutoring can enhance students’ learning achievements in mathematics at SDN Purwomartani. The C3T method emphasizes the active role of students, speed, and intelligence in learning, thereby increasing students’ motivation and mastery. Peer tutoring also helps boost the confidence of peer tutors, in addition to providing additional support and guidance to students in overcoming learning difficulties.